Induction brazing for rapid localized repair of Inconel 718 - Aprilia, A. (2022)
Vacuum furnace has been used for brazing repair of aerospace components, but it is a slow process which typically takes a few hours. The prolonged heating and cooling cycles could cause some adverse effects on the components such as excessive grain growth. A rapid brazing technique using induction coil was studied to evaluate its suitability for localized repair. Induction brazing of Inconel 718 was carried out using AMS 4777 brazing paste at different temperatures (950◦C, 1050◦C and 1150◦C) for various durations (2 min, 10 min and 20 min). Microstructure and microhardness were evaluated. The experimental results show that brazing at 1050◦C leads to desirable microstructures in a short period of merely 2 min. The study demonstrates the potential application of induction brazing for rapid localized aerospace repair.